Memahami Hukuman Salib dalam Perspektif Intertestamental sampai dengan Perjanjian Baru - Yonatan Alex Arifianto; Joseph Christ Santo (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2020)
The crucifixion of Jesus in Golgotha is an event that has an important significance in Christianity. But little is known about how crucifixion could have taken place in a Jewish environment where the matter of crucifixion was never mentioned expensively in the Old Testament. This paper intends to answer questions about the history of the penalty of the cross from the Intertestamental era to the crucifixion experienced by Jesus during the New Testament. Through literature studies, it was revealed that the punishment of the cross came from Persia adopted by the Greeks, and the Romans continued it as a punishment for the rebels by making the prisoners suffered greatly before his death. For Christianity, the punishment of the cross experienced by Jesus has more meaning than the punishment carried out by innocent people, that is as a substitute punishment that should be experienced by sinful humans. Abstrak Penyaliban Yesus di Golgota merupakan peristiwa yang memiliki makna penting dalam kekristenan. Namun tidak banyak diketahui bagaimana penyaliban bisa terjadi di lingkungan bangsa Yahudi yang mana hal penyaliban tidak pernah disebut secara ekspilis dalam kitab Perjanjian Lama. Tulisan ini bermaksud menjawab pertanyaan mengenai sejarah hukuman salib sejak era Intertestamental hingga penyaliban yang dialami oleh Yesus pada masa Perjanjian Baru. Melalui studi pustaka dikemukakan bahwasanya hukuman salib berasal dari Persia yang diadopsi oleh bangsa Yunani, dan bangsa Romawi meneruskannya sebagai hukuman bagi para pemberontak dengan membuat pesakitan sangat menderita sebelum kematiannya. Bagi kekristenan, hukuman salib yang dialami Yesus memiliki makna lebih dari sekadar hukuman yang ditangung oleh orang yang tidak bersalah, yaitu sebagai hukuman penganti yang seharusnya dialami oleh manusia yang berdosa.